Children as carers: an integrative review (Revista Latino-Americana de Enfermagem, 2012)
OBJECTIVE: to undertake an integrative literature review on the issue of "Children as carers". This is an emerging topic in the provision of health care, but nevertheless has a low profile in the literature. METHODOLOGY: this study was based in a survey of nine databases of scientific articles, using as descriptor: child, young, caregivers, lay carer and nursing role, as well as the corresponding terms in Portuguese. 21 articles were analyzed. RESULTS: these were organized into six categories - factors which motivate the child to take on the role of caregiver; these children's characteristics; tasks performed; time spent in caring; consequences of providing care and the role of the nurse in partnership with these children and their families. CONCLUSION: the children as carers are a focus of attention relevant to nursing practice, this issue representing an opportunity for investigation in Portuguese-speaking countries, as no article was found on the subject in Portuguese. In addition, with this first study in Portuguese, a work of the creation of a bibliography is begun, allowing an awareness of the issue and the identification of ways to respond to the families involved, in line with their needs.